2016
DOI: 10.1515/revneuro-2015-0039
|View full text |Cite
|
Sign up to set email alerts
|

Phosphene perception is due to the ultra-weak photon emission produced in various parts of the visual system: glutamate in the focus

Abstract: AbstractPhosphenes are experienced sensations of light, when there is no light causing them. The physiological processes underlying this phenomenon are still not well understood. Previously, we proposed a novel biopsychophysical approach concerning the cause of phosphenes based on the assumption that cellular endogenous ultra-weak photon emission (UPE) is the biophysical cause leading to the sensation of phosphenes. Briefly summarized, the visual sensation of light (phosphenes)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…As we have previously pointed out (Császár et al, 2016), there are some studies recently published (Kobayashi et al, 1999a,b;Tang and Dai, 2014b) that may support that the conclusion that cortical phosphenes are due to the glutamate-related excess biophoton emission in the retinotopic early visual parts. Regarding cortical areas, LSD mainly concentrated in the visual regions.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…As we have previously pointed out (Császár et al, 2016), there are some studies recently published (Kobayashi et al, 1999a,b;Tang and Dai, 2014b) that may support that the conclusion that cortical phosphenes are due to the glutamate-related excess biophoton emission in the retinotopic early visual parts. Regarding cortical areas, LSD mainly concentrated in the visual regions.…”
Section: Discussionsupporting
confidence: 58%
“…-MPO is not only expressed in immune cells as neutrophils and monocytes (Malle et al, 2007) but also by neurons (Green et al, 2004) and microglia. -The latest experiments (Tang and Dai, 2014b) support that the cortical phosphene lights are due to the glutamate-related excess biophoton emission in the occipital cortex (Császár et al, 2016). -When LSD stimulates 5-HT 2A receptors on glutamate axon projections from the thalamus, it can excite the cortical pyramidal cells that release glutamate ( Nichols, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Conventional understanding of the human and animal visuals systems holds that the external light signal is transformed into a neural electrical signal by the retina, and then enters into the central nervous system through the optic nerve and produces visual perception. Recent studies have found that UPE may explain some aspects of special visual phenomena [ 25 , 26 ]. There are two groups of light emissions from biological systems: induced and spontaneous [ 27 , 28 ].…”
Section: Ultraweak Photon Emission In the Retinamentioning
confidence: 99%